A chiral electrochemical system based on l-cysteine modified gold nanoparticles for propranolol enantiodiscrimination: Electroanalysis and computational modelling. (5th December 2019) - Stoian, Ioan – Adrian; Iacob, Bogdan-Cezar; Prates Ramalho, João P.; Marian, Iuliu Ovidiu; Chiș, Vasile; Bodoki, Ede; Oprean, Radu
Abstract: Enantioselective electrochemical sensors seem to hold the promise for a fast and easy alternative for the chiral probing of bioactive molecules. However, the underlying mechanism responsible for the chiral recognition is rarely known, and suitable investigational tools are dearly missed. Therefore, as a proof-of-concept, our study is focused on investigating the interaction mechanism of the enantiomers of a chiral drug molecule, namely propranolol (PRNL) with the surface of bare and l -cysteine (l -Cys) modified gold nanoparticles employing various electrochemical techniques (differential pulse voltammetry and electrochemical impedance spectroscopy) and computational modeling (molecular dynamics simulations). If the strong surface adsorption of PRNL antipodes on bare gold nanoparticles may not be exploited for enantioselective recognition, upon the functionalization of the nanostructures with l -Cys, the almost two fold increase in the oxidation current is also accompanied by a cathodic shift (∼40 mV) of the peak potential for the S(−)-enantiomer. This peak potential shift seems to be the consequence of a favored orientation of the surface adsorbed S(−)-enantiomer towards electron transfer and/or a weaker interaction with the chiral selector and thus a higher free energy of the transient diastereoisomeric complex, in comparison with its R(+)-antipode. Computational modeling highlighted the H-bond donor and acceptor atoms of both the chiral selector (l -Cys) and adsorbates (PRNL enantiomers) responsible for the recorded enantioselective electrochemical signal. Correlations between the observed electrochemical signal and enantioselective molecular interactions occurring at the surface of the electrode may lead the way towards a more rational design of future chiral electrochemical sensing platforms. Graphical abstract: Image 10619 Highlights: Insights of PRNL enantiodiscrimination at the surface of L-Cys@AuNPs provided. Molecular interactions were correlated with the chiral electrochemical signal. The main force modulating the recorded enantioselectivity is hydrogen bonding. A significantly higher number of H-bonds is developed by the adsorbed R(+)-PRNL. Computational modeling a valuable tool for the investigation of chiral interactions.